Economic voting in Poland: the end of transition model - Wojtasik, Waldemar (Political Preferences, 2013)
Research on economic voting in Poland have been carried out from the beginning of the democratic transformation, focusing on isolating and testing of the transition model specific to the countries of Central Europe. Its differen- tiating feature is a novel way of simultaneously joining the retrospective and prospective motivations in the behavior of voters, compared to the conven- tional model present in consolidated democracies. The purpose of the present article is to attempt to determine the relationship between the two types of elec- toral motivations identified above in the parliamentary elections, starting with the election of 1991 and ending with the 2011 elections. Based on analysis and constructive criticism of findings of other researchers and own research, the presented paper evidences that the validity of applying the transitional model in the study of economic voting in Poland has been exhausted, as the prospective motivation is nowadays predominant in the decisions of voters.